Some aspects of self-appraisal of six-year-old children - Vasiliauskaitė, Z. (Psichologija, 1984)
The article deals with the interrelation of learning success and the level of self-appraisal. Children whose learning success is not so great tend to appraise themselves lower than their friends whose learning success is great.